Dementia with Lewy bodies: emerging drug targets and therapeutics. (3rd June 2021) - Pope, Evans D.; Cordes, Laura; Shi, Jiong; Mari, Zoltan; Decourt, Boris; Sabbagh, Marwan Noel
ABSTRACT: Introduction: Dementia with Lewy bodies (DLB) is characterized by the toxic accumulation of α-synuclein protein inside neural cells; this results in neurodegeneration which is clinically accompanied by behavioral and psychological changes. DLB shares features with Parkinson's disease (PD) and Parkinson's disease dementia (PDD), but also overlaps neurochemically and pathologically with Alzheimer's disease. Symptomatic treatments for LBD differ in their effectiveness while disease-modifying and curative approaches are much needed. Areas covered: We explore emerging therapeutics for DLB through the lens of repurposing approved drugs and survey their potential for disease modifying actions in DLB. Given the complexity of DLB with multiple pathologies, potential therapeutic targets that could affect Lewy body pathology, or metabolism or neurotransmitters or immunomodulation were surveyed. We queried PubMed and ClinicalTrials.gov searches 2017–2020. Expert opinion: DLB is not simply aredux ofAD or PD; hence, treatments should not be exclusively duplicative ofAD or PD directed treatments. This opens amyriad of possibilities for therapeutic approaches that are disease specific or repurposed.